Programy katolickie w Radiu Poznańskim (1927-1933) i w Polskim Radiu w Poznaniu (1933-1939) - Biesiada, Jacek (Ecclesia. Studia z Dziejów Wielkopolski, 2009)
The opening of the Vatican radio station on 12 February 1931 by Pious XII marked the moment from which the Catholic Church, initially reluctant towards radio broadcasting, began to see it as a tool of evangelization. In many countries, Poland included, ways of cooperation of the Church with the radio were subsequently developed along with guidelines for preparing Catholic radio programs. The Poznań radio, which opened on 24 April 1927, already ten days later, by permission of Cardinal August Hlond, conducted the first broadcast of the Holy Mass in Poland. From then on, until the outbreak of the Second World War, the schedule of the Poznań radio station included broadcasts of the weekly Holy Mass, services, Church events as well as concerts of sacral music and programs on religious themes. The article is appended with their complete list.